Knowing from a Distance: An Improv(is)ed Dialogue About Constellations of Meaning - Deterala, Sophia; Villar, Eula Bianca (PRISM: Casting New Light on Learning, Theory and Practice, 2019)
Through a dialogical exchange about disasters, we explore the notion of “knowing” by drawing on our own experience and research about improvisation and disaster management. Locating our work within our positionalities as expatriate Filipino researchers of considerable distance/closeness from each other, we find, albeit serendipitously, how our improvisational methodologies can occur en route to, during, and in, the aftermath of crisis. Through reconstructions of the calamitous, we establish certain distances with the event itself, disaster victims, ourselves, and other improvisers of meaning such as media journalists. We propose that this network of knowing forms part of the constellational relationships of meaning-making about disasters.